The LHIN adventure: The journey continues. Issue 6 (November 2015) - Huras, Paul; Switzer, Gary; Eliasoph, Hy
The Local Health Integration Network (LHIN) adventure began 10 years ago with the intent of transforming the Ontario health system by providing system-based leadership and building collaborative capacity among health service providers. The LHIN construct has continued its evolution during this time and is still in the midst of testing and reshaping the boundaries of its mandate and authority. Working closely and in tandem with the Ministry of Health and Long-Term Care, LHINs have grappled with governance, funding, integration, and engagement, changing the nature of relationships and the dynamics inherent across the health system. The next decade holds considerable promise for LHINs and the health system in Ontario as a whole.